Are nursing students trained to meet the needs of cancer suvivors and their families? New challenges, new opportunities - Cristina García Vivar; Virginia La Rosa Salas; Marta Domingo Oslé (Universidad de Antioquia, 2019)
Current cancer treatments, along with more effective prevention measures, are producing increased cancer survival globally;(1) becoming - in many cases - a chronic disease.(2) Care of patients and families, living with a chronic disease, like cancer, constitutes one of the principal challenges for most health systems because they represent a heavy burden in terms of morbidity and mortality and carry a high percentage of the public expenditure in health.(3) Above all, the impact of cancer entails suffering and represents an important limitation in the quality of life, productivity, and functional state of the sick individuals and those living with them, that is, their family. More so, with evidence of the progressive increase of the number of older people with cancer, who are more prone to having comorbidities and other problems associated with their age, like dementia, depression, cerebrovascular accident, and diabetes.(4)